2019
DOI: 10.2196/13315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinicians' Use of Electronic Knowledge Resources on Clinical and Learning Outcomes: Systematic Review and Meta-Analysis

Abstract: BackgroundClinicians use electronic knowledge resources, such as Micromedex, UpToDate, and Wikipedia, to deliver evidence-based care and engage in point-of-care learning. Despite this use in clinical practice, their impact on patient care and learning outcomes is incompletely understood. A comprehensive synthesis of available evidence regarding the effectiveness of electronic knowledge resources would guide clinicians, health care system administrators, medical educators, and informaticians in making evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Previous research has focused on interventions to either increase the use of, or nd new ways of using, electronic knowledge sources, whereas this study speci cally examined the effect of the use of a knowledge base on patient outcome measures in two nationwide registries. Earlier studies have found that use of register data may play a vital role in patient care (12,15,36). Furthermore, an excess of research has been devoted to evaluating electronic knowledge sources by employing self-reported use, which is prone to biases (37-39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has focused on interventions to either increase the use of, or nd new ways of using, electronic knowledge sources, whereas this study speci cally examined the effect of the use of a knowledge base on patient outcome measures in two nationwide registries. Earlier studies have found that use of register data may play a vital role in patient care (12,15,36). Furthermore, an excess of research has been devoted to evaluating electronic knowledge sources by employing self-reported use, which is prone to biases (37-39).…”
Section: Discussionmentioning
confidence: 99%
“…Online knowledge bases have been shown to increase the application of evidence-based medicine in clinical practice (11)(12)(13). In this study, we used Lobach's de nition of a knowledge base: "Electronic (computer-based) resources comprising distilled (synthesized) or curated information that allows clinicians to select content germane to a speci c patient to facilitate medical decision making" (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on interventions to either increase the use of, or find new ways of using, electronic knowledge sources, whereas this study specifically examined the effect of the use of a KB on patient outcome measures in two nationwide registries. Earlier studies have found that use of register data may play an vital role in patient care (12,15,32). Furthermore, an excess of research has been devoted to evaluating electronic knowledge sources by employing self-reported use, which is prone to biases (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Lobach's definition of a KB: "Electronic (computer-based) resources comprising distilled (synthesized) or curated information that allows clinicians to select content germane to a specific patient to facilitate medical decision making" (14). The use of KBs is associated with a positive impact on clinician behavior and patient outcomes, and evidence suggests that use of KBs may be associated with improved knowledge and patient outcomes (12,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Of these questions, many are often left unanswered, as demonstrated by 3 studies in the United States where 63.8% (702/1,101), 44.9% (477/1,062), and 70.2% (207/295) of medical questions raised by clinicians were left unanswered [3][4][5]. Yet, answering clinical questions correctly has a significant impact on patient outcomes and health system efficiency [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%